The assessment on RNA quality and banana ripening genes (MaGAPDH, MaACS1, and MaACO1) from flesh tissues with different preservation methods - Annisa Amalia; Nugrahapraja, Husna (Penerbit Universiti Kebangsaan Malaysia, 2020)
The preservation of banana fruit is vital to ensure ripening quality during the transportation process. The quality of banana can be defined using the gene expression marker, which needs high-quality RNA. However, when access to the laboratory is difficult, during long-distance transportation, lack of liquid nitrogen or refrigerator, we need an alternative for preservation methods, so the sample and the extracted RNA are still in excellent conditions. Aim of our research is to find the best preservation methods and test the genes expression marker of Cavendish banana flesh tissues without using the liquid nitrogen. In this study, we performed preservation methods for RNA extraction by directly storing the flesh tissues at -80°C refrigerator and combined with the use of various flesh cutting time (0, 19, and 30 minutes). We measured the total RNA yield, absorbance ratio of 260/280, and checked the expression of MaGAPDH, MaACS1, and MaACO1 genes using Reverse TranscriptasePCR (RT-PCR). As a result, we found that the preservation methods did not affect the quality of RNA and the genes expression as well. Although the gene expression analysis need to be confirmed in future using quantitative PCR (qPCR) analysis. However, our preservation methods can be used as an alternative preservation method.